Resposta ao esqueletamento de progênies de Coffea arabica L.: produtividade e qualidade - Nadeleti, Denis Henrique Silva (2017)
The use of resistant cultivars to rust has been an important strategy in the control of this disease, and under favorable conditions to its development, rust can cause significant damage to the crop, mainly in the productivity reduction. Framewok pruning (cutting of all plagiotropic branches at 20-30 cm from the orthotropic branch) is widely used to renovate crops, eliminating unproductive plant tissue and favoring high productivity. The "Safra Zero" system began to be adopted in order to maintain the crop size and eliminate the crops in a low harvest year, recommending pruning cycles after years of high harvest. In this context, the objective was to select Coffea arabica L. progenies which are responsive to framewok pruning, present a high drinking quality potential, as well as other agronomic characteristics of interest. Eighteen progenies in the F 5 generation were evaluated, eight of them from the Catucaí group (crosses of Catuaí cultivars with coffee plants from Icatu germplasm) and ten descendants of Timor Hybrid (Red and Yellow Catuaí with Timor Hybrid), as well as two commercial cultivars as control (TupíIAC 1669-33 and ObatãIAC 1669-20). The experiment was conducted in the experimental area at the Federal University of Lavras, and pruned in August 2014. The experimental design was a randomized complete block (DBC) with three replications, with 20 treatments (18 progenies and 2 commercial cultivars) totaling 60 experimental plots. Each plot consisted of 15 plants. The following characteristics were evaluated: vegetative vigor, rust incidence (%), productivity (sack ha -1 ), fruits with empty locule (%), sieves 16 and above and 17 and above (%), grains type oval (%), coffee by total harvest, as well as aspect, sieves 16 and above and 17 and above (%), grains type oval (%) and sensory evaluation (cup test) of "natural ripe" coffee. For the statistical analyzes, the software 'Sisvar' version 5.6 was used, and the data submitted to variance analysis (ANOVA), and when significant differences were detected by the F test, the Scott-Knott test was applied at the 5% probability level. Progenies 9 (H516-2-1-1-18-1-1), 12 (H516-2-1-1-18-1-4), 16 (H419-3-4-5-2-1-3), 18 (H419-3-4-5-2-1-5) and the cultivar Tupí IAC 1669-33 were responsive to framewok pruning, exceeding the maximum productivity achieved before pruning, in the first year after pruning, and presenting a average productivity of the biennium in the "Safra Zero" system higher than the average productivity of six harvests prior to pruning. With the exception of the progenies Yellow Catucaí 24/137, all the genotypes studied presented potential for the production of special coffees. Progeny 15 (H419-3-4-5-2-1-2) and the cultivar Obatã IAC 1669-20 (control) conditioned a drink classified as excellent, standing out from the other genotypes.